Pengaruh Disiplin Dan Motivasi Kerja Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening - Aura Febriyanti; Syaiful Amri; Putri Reno Kemala sari (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
This study aims to determine the effect of work discipline, work motivation, employee performance through job satisfaction as an intervening variable at the BKKBN Kab. Dompu. This research is a quantitative research with data collection techniques using questionnaires and interviews, the sample used is 23 people with a sampling technique that is non-probability sampling. The data analysis used was path analysis using model 1 regression and model 2 regression. This research shows that work discipline has a significant effect with t-count: 3.322 greater than t-table: 2.093 with a significant level at 0.004 less than 0.05. Work motivation has no significant effect on the value of t count: -2,030 less than t table: 2.093 with a significant level at 0.057 greater than 0.05. Job satisfaction has a significant effect on the value of t count: 8.554 greater than t table: 2.093 with a significant level at 0.000 greater than 0.05. The effect of work discipline on employee performance through job satisfaction shows an insignificant effect with a value of 0.346. Meanwhile, the influence of work motivation on employee performance through job satisfaction shows a significant effect with a value of 0.283.